EVALUATION OF SLOW RELEASE FERTILIZER ON THE INITIAL DEVELOPMENT AND COFFEE PRODUCTION - Franco Junior, Kleso Silva; Carvalho, Julian Silva; Guimarães, Bernardino Cangussu; Barbosa, Camila Karen Reis; Brigante, Giselle Prado; Dias, Marcio de Souza; Aprelini, André; Silva, Nilton de Oliveira (Coffee Science - ISSN 1984-3909, 2019)
The objective in this work was to evaluate the efficiency of slow release fertilizer in seedling production, initial development and first coffee production. The research was carried out at Sitio Santa Felicidade, Campestre - MG, Brazil, in a randomized block design with two treatments and ten replicates, totaling 20 experimental plots. Coffee seedlings were produced using Ciclus Substrate (20% N, 22% P2O5 and 5% K2O) and conventional fertilizers 4 kg simple super phosphate (18% P2O5) and 0.25 kg Potassium Chloride (58% K2O). The variables evaluated were size, dry and fresh matter of the shoot and root system, and the seedlings were transplanted to the field and those from Ciclus Substrate received in the first year Ciclus NS (30% N) and in the second year. NK (19-00-19) and conventionally produced with conventional fertilizers (20-00-20 and 25-00-25 respectively), the variables evaluated were: shoot growth, length and number of plagiotropic branch internodes Slow release fertilizer ciclus Substrate has been found to be a viable technology for the production of arabica coffee seedlings, coffee planting NS provides good plant development and coffee producing NK provides good plant growth and higher productivity.